ANALISIS OVERLAY SEKTOR UNGGULAN PROVINSI BANTEN - Suhandi Suhandi; Nisrina Hakin (LP2M Universitas Bina Bangsa, 2021)
Banten Province is one of the provinces that had economic growth contracted during the Covid-19 Pandemic. Banten's economic growth rate has always increased from year to year in the last decade except 2020, but does not eliminate the potential from economic categories, especially those that fall into the leading and potential categories. The existence of a good economic development strategy and in accordance with regional conditions is expected to be able to encourage and increase the rate of economic growth of Banten Province. This research aims to analyze the leading economic sectors in order to be inputs for local governments in implementing economic policies in the future. This research uses several analytical techniques, namely Sector Contribution Analysis, Growth Rate Analysis, Location Quotient Analysis (LQ), Shift-Share Analysis, Growth Ratio Model Analysis (MRP) and Klassen Typology, then concluded using Overlay Analysis. The results showed that Banten Province has seven leading categories where five categories with rapid growth and two categories experienced depressed growth. The five categories are Water Procurement, Waste Management, Waste and Recycling (E), Large trade and retail, Car and Motorcycle Repair (G), Information and Communication (J), Real Estate (L), and Health services and Social Activities (Q). While the other two leading categories are Processing Industry (C) and Transportation and Warehousing (H). The economy of Banten Province received a positive result on the total performance value during the period 2010-2020 because it experienced an absolute increase in value of 62.56 percent.